2015
DOI: 10.3390/toxins7020299
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Toxin OrtT (YdcX) of Escherichia coli Reduces Growth during the Stringent Response

Abstract: Toxin/antitoxin (TA) systems are nearly universal in prokaryotes; toxins are paired with antitoxins which inactivate them until the toxins are utilized. Here we explore whether toxins may function alone; i.e., whether a toxin which lacks a corresponding antitoxin (orphan toxin) is physiologically relevant. By focusing on a homologous protein of the membrane-damaging toxin GhoT of the Escherichia coli GhoT/GhoS type V TA system, we found that YdcX (renamed OrtT for orphan toxin related to tetrahydrofolate) is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 78 publications
(94 reference statements)
1
21
0
Order By: Relevance
“…It is now clear that the fitness of bacteria is enhanced if they are able to reduce their metabolism during stress. For example, membrane toxin GhoT (Wang et al, ) reduces cell growth by decreasing ATP production and the proton motive force during antibiotic stress to make the cell more fit (Cheng et al, ), and membrane toxin OrtT reduces cell growth by reducing ATP during the stringent response (e.g., nutrient stress) to make the cell more fit (Islam et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is now clear that the fitness of bacteria is enhanced if they are able to reduce their metabolism during stress. For example, membrane toxin GhoT (Wang et al, ) reduces cell growth by decreasing ATP production and the proton motive force during antibiotic stress to make the cell more fit (Cheng et al, ), and membrane toxin OrtT reduces cell growth by reducing ATP during the stringent response (e.g., nutrient stress) to make the cell more fit (Islam et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Of these genes, phage shock protein ( pspC ) has been reported to be involved in indole-mediated persister formation (Vega et al, 2012b). And ydcX also participates in persister formation as an orphan toxin (Islam et al, 2015), and ssrA involved in trans-translation has previously been shown to be involved in persister formation (Li et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The 13 overlapping genes of S2/S1 and S3/S1 were supposed to be of significance for both “boot-up” and “shoot-up” of persister formation and required a thorough investigation. Apart from two genes ( ssrA and ydcX ) which have been known to participate in the persister formation (Li et al, 2013; Islam et al, 2015), the other 11 overlapping genes have not been reported to be related to persistence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations